An Interesting Association of Cystic Hygroma of the Neck and Lymphangioma Causing a Paediatric Swollen Tongue - A. N. Beech; J. N. Farrier (Hindawi Limited, 2016)
Up to 75% of lymphatic malformations occur in the head and neck region. Of these, cystic hygromas and lymphangiomas have been widely reported; however they rarely occur in the same patient. We report the case of a 5-year-old girl who presented to the Department of Paediatrics of a district general hospital with a short history of recurrent, painful swelling of the anterior one-third of her tongue. She was reviewed under the joint care of the Oral and Maxillofacial Surgery and Otolaryngology Teams. Relevant past medical history included a previously excised cystic hygroma from her right neck when she was aged 2 years. Diagnosis of lymphangioma was made and of the potential management options available active monitoring was favoured due to the patient's age. To our knowledge the occurrence of both tongue lymphangioma and cystic hygroma has not been previously reported in a paediatric patient. This case report therefore shows a rare association between a cystic hygroma of the neck and lymphangioma of the tongue.